STUDI TENTANG KESELARASAN LINGKUNGAN BISNIS, STRATEGI MANUFAKTUR, DAN KINERJA OPERASIONAL PADA PERUSAHAAN MANUFAKTUR DI INDONESIA - Lina Anantan (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2008)
Expanding global competition, rapidly changing market and technology, increasing complexity and uncertainty are causing manufacturing firm to examine a shift from industrial system driven by efficiency to post industrial system where success depend on quick response to customer demand for customized and high quality product. In the post-industrial environment, high quality and reliability, timely delivery, enhance customer service, rapid new product introduction, flexible system, and efficient capital deployment, are primary source of competition. In order to response this condition, manufacturing organizations must adopt and implement manufacturing strategy if they want to stay competitive. In this manufacturing strategy formulation process, environmental considerations appear to play significant role in the determination of the content of manufacturing strategy. This research was conducted to investigate the relationship amongst environment uncertainty, manufacturing strategy, and firm performance. Data are collected through mailed questionnaire (525 questionnaires) and direct survey to 25 firms. The total questionnaires are sent to 550 CEOs manufacturing firm in Indonesia. A hundred and six responses are returned yielding response rate 19.27%. The study finds relationship between environmental factors such as business cost, labor availability, competitive hostility, and dynamism in the market, and the manufacturing strategy choices encompassed by competitive priorities. But this study did not find significant relationship between manufacturing strategy and operational operation.Keywords: environmental uncertainty, manufacturing strategy, firm performance